2016
DOI: 10.4236/msa.2016.72009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Additions in the Use of Glass Fibre Reinforced Cement as a Construction Material

Abstract: Although in recent years glass fibre reinforced cement (GRC) has been used in buildings and infrastructure, its application in structural elements has been somewhat restricted due to the worsening of its mechanical properties with ageing and the limited data available related with its fracture energy. With the aim of developing existing knowledge of GRC, the fracture energy in an in-plane and out-of-plane direction of the panel has been obtained. Three types of GRC with different formulations have been tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The tensile stress-strain constitutive relationship which is determined from Eqs. (1) and (2) and the experimental mechanical material's parameters already identified (Table 8) is illustrated in Fig. 14-a.…”
Section: Identification Of Model Parameters Of Gfrcmentioning
confidence: 94%
See 2 more Smart Citations
“…The tensile stress-strain constitutive relationship which is determined from Eqs. (1) and (2) and the experimental mechanical material's parameters already identified (Table 8) is illustrated in Fig. 14-a.…”
Section: Identification Of Model Parameters Of Gfrcmentioning
confidence: 94%
“…GFRC is a composite material produced by reinforcement of a cementitious matrix in which short length glass fibers are distributed randomly. The incorporation of glass fibers is getting growing interest as it offers many advantages such as light weight and mechanical performance which has proved high compressive and tensile strengths, toughness and energy absorption [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was quickly observed that ordinary borisilicate glass fibers (E-glass) are eroded due to the alkalinity of the cement paste. The corrosion of the fibers in the cement matrix causes a phenomenon commonly known as ageing of glass fibers in the cement matrix: the ductility and the enhancement of the mechanical properties of the composite decrease with time [ 60 , 61 ]. Considerable effort was made to develop alkali-resistant glass fibers, until this problem was practically solved by the addition of zircon oxide ZrO 2 developed by Majumdar and Ryder in 1968 [ 11 ].…”
Section: Fibersmentioning
confidence: 99%
“…The stress-strain response revealed enhancement in post peak with increasing fiber dosage at all exposure temperatures. Enfedaque et al [28] used DIC technique in the fracture test analysis of glass fibre reinforced cement (GRC). The damage pattern from the DIC output in the fracture tests of the GRC (with an addition of 25% of the thermal-treated kaolin) explained the higher fracture energy found in this admixture and is proved to be the most suitable formulation for possible future structural applications.…”
Section: Introductionmentioning
confidence: 99%